Student perceptions of GenAI as a virtual tutor to support collaborative research training for health professionals - Jacqueline E. McLaughlin; Cory Dal Ponte; Kayley Lyons (BMC Medical Education)
Abstract Background Research and evaluation skills are essential in healthcare education. Instructors frequently employ collaborative learning models to teach these competencies; however, delivering timely and personalized feedback to multiple groups can be a significant challenge. This study aimed to investigate the potential of generative artificial intelligence (GenAI) as a tool for providing feedback on students’ research ideas. Methods We employed GenAI tools to provide personalised formative feedback during a small-group activity focused on helping students formulate research plans. The activity was implemented within two university courses designed for working health professionals. Students were grouped into groups of 5–7 students and provided clear instructions for how to prompt the GenAI for feedback on their research ideas. Participants completed an evaluation survey at the end of the activity that assessed frequency of use, perceived value, utility, and overall satisfaction. Results Half of the participants (n = 64, 85.3% response rate) had never used GenAI before (n = 32). Participants agreed or strongly agreed that the feedback provided by the GenAI was valuable (n = 54, 85%), helped them improve their plan (n = 50, 78%), and increased their interest in GenAI (n = 55, 86%). Participant comments described the feedback as favourable, specified an interest in adapting their plan, and rarely indicated a lack of trust or disagreement with the feedback provided. Conclusions GenAI offers an efficient and satisfactory approach to providing feedback to students for their research ideas. As a supportive tool, GenAI may foster student learning while enabling educators to rethink how and what they focus their time on, with an eye toward helping students understand more nuanced and complex research concepts. This study highlights the potential of GenAI as a virtual tutor, and the need for additional research to explore its benefits and challenges.